2002
DOI: 10.1161/01.hyp.0000037969.41360.cc
|View full text |Cite
|
Sign up to set email alerts
|

PPARα Activator Effects on Ang II–Induced Vascular Oxidative Stress and Inflammation

Abstract: Abstract-Docosahexaenoic acid (DHA), a peroxisome proliferator-activated receptor-␣ (PPAR␣) activator, reduces blood pressure (BP) in some hypertensive models by unclear mechanisms. We tested the hypothesis that DHA would prevent BP elevation and improve vascular dysfunction in angiotensin (Ang) II-infused rats by modulating of NADPH oxidase activity and inflammation in vascular wall. Sprague-Dawley rats received Ang II (120 ng/kg per minute SC) with or without DHA (2.5 mL of oil containing 40% DHA/d PO) for 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
171
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 220 publications
(179 citation statements)
references
References 44 publications
8
171
0
Order By: Relevance
“…6 K Studies confirmed that oxidative stress has a central role in altered endothelial function by changes in nitric oxide (NO) biosynthesis. 25 What this study adds K No studies regarding the associations of reactive oxygen species (ROS) with blood pressure and arterial stiffness have been done in black South Africans. K Oxidative stress contributes to increased blood pressure in African men, especially hypertensive men.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 K Studies confirmed that oxidative stress has a central role in altered endothelial function by changes in nitric oxide (NO) biosynthesis. 25 What this study adds K No studies regarding the associations of reactive oxygen species (ROS) with blood pressure and arterial stiffness have been done in black South Africans. K Oxidative stress contributes to increased blood pressure in African men, especially hypertensive men.…”
Section: Discussionmentioning
confidence: 99%
“…25 It is clear that one could not pinpoint a specific factor contributing to the onset and/or maintenance of hypertension, but rather explore the vast collection of contributing factors. It is evident from this study that ROS seems to have a role in cardiovascular dysfunction, as reflected by the association with SBP and PP in the men.…”
Section: Discussionmentioning
confidence: 99%
“…Under pathological conditions, increased ROS bioactivity leads to endothelial dysfunction, increased contractility, vascular smooth muscle cells growth, monocyte invasion, lipid peroxidation, inflammation, and increased deposition of extracellular matrix proteins, important factors in hypertensive vascular damage. 27,28 Despite the preponderance of evidence for the association of increased oxidative stress with various vascular diseases, using antioxidants to prevent CVD has produced mixed outcomes. 29,30 This article highlights current developments in the field of ROS and hypertension, focusing specifically on the role of oxidative stress in hypertensionassociated vascular damage.…”
Section: Discussionmentioning
confidence: 99%
“…22,23 The fixative was washed from the organ bath by repeated changes with PBS (pH 7.4) and finally washed with PBS containing 0.1% Triton X-100 (pH 8.0). Arteries were incubated with 0.5% BSA/PBS for 5 minutes at 42°C.…”
Section: Laser Confocal Microscopymentioning
confidence: 99%